Characterization of the user population and the diagnosis of the individual consultation of Nursing in Mental Health, in the area of Health San Sebastián- Paso Ancho, Costa Rica. - Araya Solís, Mauren (2020)
Introduction: The World Health Organization has evidenced in recent years an increase in the affectation of the Mental Health of people, hence the need to carry out studies aimed at understanding and characterizing the population that attends health services and in this specific case, the individual consultation of Mental Health nurses. Methodology: Quantitative approach of descriptive type, 262 records of scheduled appointments were used for this consultation. The primary source of information was the database of mental health nurses and the Single Digital Health Record (EDUS). For data analysis, basic descriptive statistics were applied. Results: It is determined that the average age of the user is 42 years, there is a predominance of female sex, with marital status "single" and incomplete secondary. It is identified that the main diagnosis of Mental Health Nursing that affected women was "problems related to the family and the home" with 52.1 % and in the case of men it was "difficulty in coping with stressors" with 41.5 %. Conclusions: individual Mental Health Nursing consultation stands out as a resource for the health service user population, because these spaces offer the opportunity to produce a change that favors effective coping strategies in the face of problematic situations of daily life.